2000
DOI: 10.1523/jneurosci.20-21-08209.2000
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Release and Uptake Dynamics within Nonhuman Primate StriatumIn Vitro

Abstract: The putamen of the human striatum is a heterogeneous nucleus that contains the primary site of loss of dopamine (DA) in Parkinson's disease (PD). Furthermore, different functional domains of the putamen are heterogeneously susceptible to DA loss, and yet the dynamic regulation of extracellular DA concentration ([DA] o ) and comparison between domains has not been explored in the primate brain. In these studies, DA was measured in real time using fast-scan cyclic voltammetry at a carbon-fiber microelectrode in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
112
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(127 citation statements)
references
References 71 publications
15
112
0
Order By: Relevance
“…Although previous work had shown that dopamine release and uptake share many characteristics in the putamen and caudate, there seems to be a continuum of distinct functional domains from ventral to dorsal areas within these two brain regions, with dopamine release and uptake being significantly greater in the dorsal compared with the ventral regions (Cragg et al, 2000(Cragg et al, , 2002. We therefore investigated ␣3/␣6␤2* and ␣4␤2* nAChR-modulated functional properties in the ventral and dorsal striatal areas, with a focus on the putamen because it is more vulnerable in Parkinson's disease (Hornykiewicz, 2001).…”
Section: ␣3/␣6␤2* Nachr Blockade Results In a Major Decrease In Evokementioning
confidence: 83%
See 1 more Smart Citation
“…Although previous work had shown that dopamine release and uptake share many characteristics in the putamen and caudate, there seems to be a continuum of distinct functional domains from ventral to dorsal areas within these two brain regions, with dopamine release and uptake being significantly greater in the dorsal compared with the ventral regions (Cragg et al, 2000(Cragg et al, , 2002. We therefore investigated ␣3/␣6␤2* and ␣4␤2* nAChR-modulated functional properties in the ventral and dorsal striatal areas, with a focus on the putamen because it is more vulnerable in Parkinson's disease (Hornykiewicz, 2001).…”
Section: ␣3/␣6␤2* Nachr Blockade Results In a Major Decrease In Evokementioning
confidence: 83%
“…Moreover, this anatomical diversity is associated with heterogeneity in striatal dopamine function (Cragg et al, 2000;McCallum et al, 2006b). The heterogeneous nature of the putamen is further illustrated by findings that there is a clear ventral-to-dorsal gradient in striatal dopaminergic cell loss with denervation (Song and Haber, 2000;McCallum et al, 2006b).…”
mentioning
confidence: 99%
“…[60][61][62] The dynamics of dopamine release, uptake kinetics, regulation by firing frequency and presynaptic autoreceptor function in the human striatum, which consists of a distinct caudate nucleus and putamen, also differs considerably from rodent striatum. 63,64 Hence, the pharmacological response in cortical or striatal sites to antipsychotic drugs may be different in primate brain than in mouse brain resulting in potentially different transcriptome profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Although stimulation-evoked release has been measured from monkey striatum in vitro using voltammetry (Cragg et al, 2000) and, more recently, nicotine-stimulated release has been measured in vivo with positron emission tomography (Marenco et al, 2004), nicotine-evoked [ 3 H]dopamine release from synaptosomes has not previously been studied using monkey brain, although this approach is widely used with rodent preparations (Wonnacott, 1997;Grady et al, 2001;Champtiaux et al, 2003;Quik et al, 2003). Because this technique offers the advantage that it allows for the quantitative determination of evoked-release under well defined experimental conditions, we conducted experiments to establish its feasibility using monkey synaptosomes.…”
Section: Characterization Of Nicotine-evoked [ 3 H]dopamine Release Fmentioning
confidence: 99%
“…Stimulation-evoked release has previously been measured from control monkey striatum in vitro using voltammetry (Cragg et al, 2000); nicotine-stimulated release has been measured in vivo with positron emission tomography (Marenco et al, 2004). However, nicotine-evoked […”
mentioning
confidence: 99%